MODEL PEMBELAJARAN LOMPAT TALI UNTUK MENINGKATKAN HASIL BELAJAR LOMPAT TINGGI GAYA STRADDLE PADA SISWA KELAS V SD NEGERI SIDAKAYA 06 KABUPATEN CILACAP TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Physical education in schools especially in learning the high jump straddle styles not applied variations inteaching or monotous, so that student are saturted, passion, and lot of student who do not meet the criteriaspecified mastery learning in schools, 75. Problems in this study is “ How jump rope learning model to improvelearning outcomes straddle style high jump in class V on junior high school sidakaya 06 Cilacap distictacademic year 2012/2013 ?” as for the purose of this study was to determine the jump rope learning model toimprove learning outcomes straddle style high jump in class V on junior high school sidakaya 06 Cilacap distictacademic year 2012/2013. Type of reserch is a class act. Subject used to use student data class V junior highschool sidakaya 06 numbered 29. Data collection techniques using student questionnairs that include cognitive,affective, and psychomotor. Data analysis using descriptive qualitive. Of the research results obtained in cycle I data on student mastery learning as many as is student or 51,72% and students who have not completed a totalof 14 categories of students or 38,28%. While the second cycle students mastery learning result obtained by 26students or 89,65% and students who have not completed as much as 3 categories of students or 10,35%. Of theresearch cycle I to cycle II has been an increase in the classical style which II students (37,93%), so it can besaid that model of learning to jump rope to improve learning outcomes in the high jump straddle style grade 5students sidakaya 06 junior high school succeded as much as 89,65%. Conclusions of this research is modeledstraddle style learning the high jump with a jump rope games can improve student learning outcomes becauseacording to the character of the students grades and learning PAIKEM. So the researchers delivered,suggestions that :1) For school teachers is expected to increase the quality and the quality and the quality oflearning for students and teachers to improve the quality, 2) teachers are expected to be more innovative inapplying the method to deliver the learning, 3) to enhance students learning spirit in any condition, becauselearning to play media that can improve intelligence and healt.